Association Between Changes in Caregiver Depressive Symptoms and Child Attention-Deficit/Hyperactivity Disorder Symptoms. Issue 5 (June 2018) - Walls, Morgan; Cabral, Howard; Feinberg, Emily; Silverstein, Michael
ABSTRACT: Objective: Depression is highly prevalent among caregivers of children with attention-deficit/hyperactivity disorder (ADHD). We examined the association between caregiver depressive symptom trajectories and changes in child ADHD symptoms. Methods: We analyzed data from a randomized trial of 2 ADHD care management systems for children aged 6 to 12 years and their caregivers (n = 156 dyads). Child ADHD symptoms were measured using the Swanson, Nolan, and Pelham rating scale (SNAP-IV). Caregiver depressive symptoms were measured using the Quick Inventory of Depressive Symptomatology (QIDS). Measures were assessed at baseline, 6 months, and 12 months. We used multivariable models to examine associations between changes in caregiver depressive symptoms and changes in child ADHD symptoms. Results: From baseline to 12 months, children of caregivers with improved depressive symptoms had significantly greater reductions in SNAP-IV scores (change score: −1.43) compared with those whose depressive symptoms did not change (change score: −0.97) or worsened (change score: −0.23, p = 0.003). In adjusted models, improved caregiver depressive symptoms were associated with greater reductions in SNAP-IV scores over the 12-month period. Compared with those with worsening caregiver depressive symptoms, children whose caregivers showed no significant changes in depressive symptoms had a −0.78 point (95% confidence interval [CI]: −1.40 to −0.17) greater reduction in the SNAP-IV score, and those children whose caregiver depressive symptoms improved had a −1.31 point greater reduction in the SNAP-IV score (95% CI: −1.97 to −0.66). Conclusion: Given the longitudinal association between caregiver depressive symptom and child ADHD symptom trajectories, interventions that address the behavioral health needs of the family unit may offer promise for urban children with ADHD.